Penetapan Tersangka Terhadap Korban Tindak Pidana Pencurian Yang Melakukan Pembelaan Terpaksa (Noodweer) Dalam Hukum Pidana Indonesia - Nanang Tomi Sitorus; Fitria Ramadhani Siregar; Wenggedes Frensh (Faculty of Law, Universitas Riau, 2021)
The abolition of crime is divided into two parts, namely those listed in the law and the other being outside the law, introducing jurisprudence and doctrine. The elimination of the crime, namely the forced defense (noodweer) has become a hot topic in the criminal law enforcement process in Indonesia. A forced defense (noodweer) is only carried out when a person feels that he or she is in danger or under threat. However, in some cases, many misunderstood the noodweer defense, so this raises pros and cons. The type of research carried out in this research is normative or doctrinal juridical research aimed only at written regulations and other legal materials. For this reason, this study will discuss the position of forced defense against victims of theft crime who are suspects and the ability to be responsible for victims of theft crimes who are designated as suspects in forced defense.